2018
DOI: 10.1152/ajpheart.00637.2017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pulse pressure on cerebrovascular events leading to age-related cognitive decline

Abstract: Aging is a modern concept: human life expectancy has more than doubled in less than 150 yr in Western countries. Longer life span, however, reveals age-related diseases, including cerebrovascular diseases. The vascular system is a prime target of aging: the "wear and tear" of large elastic arteries exposed to a lifelong pulsatile pressure causes arterial stiffening by fragmentation of elastin fibers and replacement by stiffer collagen. This arterial stiffening increases in return the amplitude of the pulse pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 140 publications
3
89
0
Order By: Relevance
“…The consequences of large elastic artery stiffening are becoming increasingly appreciated, as described in previous reviews (Mitchell, 2008;O'Rourke & Safar, 2005;Thorin-Trescases et al, 2018). In particular, mounting evidence suggests an association between greater large elastic artery stiffness and lower cerebral blood flow, in addition to cognitive impairment and Alzheimer's disease (Jefferson et al, 2018;Knutsen et al, 2018;Meyer et al, 2017;Mitchell et al, 2011;Oh et al, 2016;Pase et al, 2016;Tarumi et al, 2011).…”
Section: Clinical Importance Of Large Elastic Artery Stiffness and Thmentioning
confidence: 83%
See 3 more Smart Citations
“…The consequences of large elastic artery stiffening are becoming increasingly appreciated, as described in previous reviews (Mitchell, 2008;O'Rourke & Safar, 2005;Thorin-Trescases et al, 2018). In particular, mounting evidence suggests an association between greater large elastic artery stiffness and lower cerebral blood flow, in addition to cognitive impairment and Alzheimer's disease (Jefferson et al, 2018;Knutsen et al, 2018;Meyer et al, 2017;Mitchell et al, 2011;Oh et al, 2016;Pase et al, 2016;Tarumi et al, 2011).…”
Section: Clinical Importance Of Large Elastic Artery Stiffness and Thmentioning
confidence: 83%
“…Likewise, our previous studies in these mice found that greater large elastic artery stiffness led to impaired endothelium‐dependent dilatation in MCAs, but not GFAs (Walker et al., ). The reason for the apparent greater vulnerability of cerebral arteries to increased large elastic artery stiffness is unknown, but potential mediators might include the higher resting blood flow in the brain (Mitchell, ), the thinner arterial wall and lack of external elastic lamina in cerebral resistance arteries (Thorin‐Trescases et al., ; Walker et al., ), or the closeness to the heart, at least compared with skeletal muscle feed arteries in the leg. It is also important to consider the role of autoregulation by cerebral resistance arteries in maintaining constant cerebral blood flow (Mitchell, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in this experiment, we explored the differences between the BCAS and BCAO models and tried to explain these differences with respect to microcirculatory dysfunction. Cerebral microcirculatory dysfunction is one of the common pathologies associated with vascular cognitive impairment (De Silva and Faraci, 2016), which causes changes in white matter lesions (Iadecola et al, 2019) and cognitive dysfunction (Thorin-Trescases et al, 2018). For example, Kitamura et al used spontaneously hypertensive rats as a model of early-stage cerebral small vessel disease.…”
Section: Discussionmentioning
confidence: 99%